Application of Intraoperative CT-Ultrasound Fusion Imaging in Hip Endoscopy for Treatment of Iatrogenic Impingement Due to PLLA Screw: A Novel Surgical Technique - Kazuma Miyatake, M.D., Ph.D.; Hyonmin Choe, M.D., Ph.D.; Fujisawa Takahiro, M.D.; Yuusuke Kawabata, M.D., Ph.D.; Yohei Kusaba, M.D.; Yutaka Inaba, M.D., Ph.D. (Arthroscopy Techniques, 2023)
Ultrasound-assisted surgery is becoming an established tool in the medical field. The addition of imagery to ultrasound-assisted surgery may enable one to perform a procedure in a safer and more accurate manner. This can be achieved through fusion imaging (fusion), a technology that synchronizes MRI or CT images with ultrasound images. We describe intraoperative CT-ultrasound fusion-guided (or -assisted) hip endoscopy for the removal of an impinging poly L-lactic acid screw, which was difficult to identify on fluoroscopy during surgery. The fusion technology enables merging two advantages of ultrasound: the real-time guidance capabilities and CT or MRI and the bird's eye view that makes minimally invasive arthroscopic and endoscopic surgery less invasive, precise, and safe.